Olive Oil Consumption and Age-Related Macular Degeneration: The Alienor Study. - Audrey Cougnard-Grégoire; Bénédicte M J Merle; Jean-François Korobelnik; Marie-Bénédicte Rougier; Marie-Noëlle Delyfer; Mélanie Le Goff; Cécilia Samieri; Jean-François Dartigues; Cécile Delcourt (PLoS ONE, 2016)
Olive oil provides a mixture of lipids and antioxidant nutrients which may help preventing age-related diseases such as age-related macular degeneration (AMD). However, little is known about the associations between olive oil consumption and the risk of AMD.To examine associations between olive oil use and AMD prevalence in elderly subjects.Alienor (Antioxydants, Lipides Essentiels, Nutrition et maladies OculaiRes) is a population-based study on eye diseases performed in elderly residents of Bordeaux (France). In 1999-2000, frequencies of consumption of main categories of dietary fats used were collected. In 2006-2088, AMD was graded from non mydriatic retinal photographs into three exclusive stages: no AMD, early AMD, and late AMD. Two categories of preferred dietary fat used (olive oil, n-3 rich oils, n-6 rich oils, mixed oils, butter and margarine) were defined: "no use" and "regular use" (using fat for spreading and/or cooking and/or dressing). Associations of AMD with each fat use were estimated using Generalized Estimating Equation logistic regressions models.Our study included 654 subjects (1269 eyes) with complete data (n = 268 eyes with early AMD and n = 56 with late AMD). After adjustment for potential confounders, regular use of olive oil was significantly associated with a decreased risk of late AMD (odds ratio [OR] = 0.44, 95% confidence interval [CI]: 0.21;0.91). In contrast, regular use of olive oil was not significantly associated with early AMD (OR = 0.84, 95%CI: 0.59;1.21). No associations were found between regular consumption of n-3 rich oils, n-6 rich oils, mixed oils, butter and margarine and AMD, whatever the stage.This study suggests a protective effect of olive oil consumption for late AMD in this elderly community-dwelling population. Characterization of the mediating nutrients deserves further research.